PERANCANGAN APLIKASI SERIKAT PEKERJA FEDERASI SERIKAT PEKERJA METAL INDONESIA CABANG MAKASSAR BERBASIS ANDROID - Ayu Lestari Perdana; Nur Isnayanti Burhanuddin; Samsul Buhaeril; Ridwan (Fakultas Teknik Universitas Islam Makassar, 2026)
The Federation of Indonesian Metal Workers Unions (FSPMI) plays a significant role in protecting the rights and interests of its members. FSPMI still faces several issues in terms of administration and storage management. This study aims to design and implement an Android-based union application to manage administration and other activities more easily and quickly. This research method uses a method based on the Waterfall and Blackbox models which aims to provide a clear structure and stages and help manage projects systematically. The application design process is carried out using flowcharts and context diagrams. This application is built using the PHP and Dart programming languages with the Laravel and Flutter frameworks, while MySQL is used as a database. The test results were carried out using the blackbox method which focuses on system functionality. The test results show that all application features function according to the designed specifications. The application has two main types of access: users (members) and admins. Users can register, view monthly dues information and input complaints through the Android application. While the admin has primary access to manage user (member) data, member complaints, member dues and financial reports. The application can facilitate users (members) and admins in managing administrative activities so that it will increase productivity, efficiency, and member engagement. Thus, this Android-based trade union application was successfully implemented and provided an effective solution in managing the administration of the Makassar branch of the Indonesian Metal Workers Federation.